Oil price benchmarks in international trade: a new US crude benchmark emerges - Caddy, P (Oxford Institute for Energy Studies, 2012)
Over the past year the price of West Texas Intermediate (WTI), the main crude price reference in the United States, has shown record discounts to North Sea Brent, the main crude price reference in Europe. This was widely expected by the industry but caught many others by surprise.